The role of polytherapy in the management of epilepsy: suggestions for rational antiepileptic drug selection. (1st February 2020) - Verrotti, Alberto; Tambucci, Renato; Di Francesco, Ludovica; Pavone, Piero; Iapadre, Giulia; Altobelli, Emma; Matricardi, Sara; Farello, Giovanni; Belcastro, Vincenzo
ABSTRACT: Introduction : Antiepileptic polytherapy may be indicated in patients experiencing drug-resistant epilepsy. To date, there are no evidence-based criteria on how to combine different antiepileptic drugs (AEDs) together, in order to obtain the best therapeutic response. Areas covered : This paper reviews the available data about the various associations of AEDs in patients undergoing polytherapy, focusing on the most effective and well-tolerated polytherapies. Moreover, some controversial aspects of this topic are addressed. Expert opinion : Nowadays, there are no guidelines on polytherapy in patients with epilepsy; thus, the management of pharmacoresistant epilepsy is still uncertain, except for valproate/lamotrigine combination, which seems to be the only one recommended. Data regarding mechanism of action, pharmacokinetics, tolerability, and, more importantly, the analysis of the valuable clinical studies of drug combinations can help physicians to choose the best and most effective AED association for each patient.